A Luminescent Metal–Organic Framework Thermometer with Intrinsic Dual Emission from Organic Lumophores. Issue 13 (11th February 2016) - Zhang, Hao; Lin, Chensheng; Sheng, Tianlu; Hu, Shengmin; Zhuo, Chao; Fu, Ruibiao; Wen, Yuehong; Li, Haoran; Su, Shaodong; Wu, Xintao
Abstract: A new mixed‐ligand metal–organic framework (MOF), ZnATZ‐BTB, has been constructed as a luminescent ratiometric thermometer by making use of the intrinsic dual emission at cryogenic temperatures. Its twofold interpenetrated network promotes the Dexter energy transfer (DET) between the mixed organic lumophores. The temperature‐dependent luminescent behavior arises from the thermal equilibrium between two separated excited states coupled by DET, which is confirmed by Boltzmann distribution fitting. The small excited‐state energy gap allows ZnATZ‐BTB to measure and visualize cryogenic temperatures (30–130 K) with significantly high relative sensitivity (up to 5.29 % K −1 at 30 K). Moreover, it is the first example of a ratiometric MOF thermometer the dual emitting sources of which are widely applicable mixed organic ligands, opening up new opportunities for designing such devices. Abstract : Cryogenic detection : The intrinsic photophysical property of cryogenic temperature can be taken advantage of to fabricate a luminescent metal–organic framework ratiometric thermometer (see structure) with dual emission arising from the Dexter energy transfer process between mixed organic lumophores.